ChemInform Abstract: The Greenish‐Blue Emission and Thermoluminescent Properties of CaTa2O6:Pr3+. Issue 14 (8th April 2014) - Noto, L. L.; Chithambo, M. L.; Ntwaeaborwa, O. M.; Swart, H. C.
Abstract Polycrystalline CaTa2O6:Pr3+ phosphor is prepared by calcination of a stoichiometric mixture of Ta2O5 and CaCO3 plus a 0.5 mol% PrCl3 dopant level (1200 °C, 4 h).